2004
DOI: 10.1063/1.1711596
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation chemistry of hydrogen halides in water

Abstract: To understand the mechanism of aqueous acid dissociation, which plays a fundamental role in aqueous chemistry, the ionic dissociation of HX acids (X=F, Cl, Br, and I) in water clusters up to hexamer is examined using density functional theory and Møller-Plesset second-order perturbation methods (MP2). Further accurate analysis based on the coupled clusters theory with singles and doubles excitations agrees with the MP2 results. The equilibrium structures, binding energies, electronic properties, stretching fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
118
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 46 publications
16
118
1
Order By: Relevance
“…In those studies, the fragments' translational energy distributions were measured, allowing for the determination of the dimer's dissociation energy (D 0 ), which was reported to be 1334 ± 10 cm −1 . 1 Previous theoretical studies 19,21,36,37 have reported values of D 0 ; at the highest level of theory, CCSD/aug-cc-pVDZ+, 19 with an approximate anharmonic zero-point energy (ZPE) calculated from MP2/aug-cc-pVDZ+, a value of 1189 cm −1 was reported. This is not in good agreement with experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In those studies, the fragments' translational energy distributions were measured, allowing for the determination of the dimer's dissociation energy (D 0 ), which was reported to be 1334 ± 10 cm −1 . 1 Previous theoretical studies 19,21,36,37 have reported values of D 0 ; at the highest level of theory, CCSD/aug-cc-pVDZ+, 19 with an approximate anharmonic zero-point energy (ZPE) calculated from MP2/aug-cc-pVDZ+, a value of 1189 cm −1 was reported. This is not in good agreement with experiment.…”
mentioning
confidence: 99%
“…[19][20][21][22][36][37][38] The global minimum with labeled coordinates is shown in Figure 1. As seen, this has a non-planar structure and, as can be surmised, there is an equivalent nonplanar minimum with a planar C 2v saddle-point connecting them through a bend of the θ 2 angle and a slight bend in the θ 3 angle.…”
mentioning
confidence: 99%
“…In the first place, the obvious factor is the number of water molecules in the cluster (hereafter hydration number). It is known that increasing hydration number enhances proton transfer in anionic systems, 36,37 as well as in neutral aggregates of water and one acid (HCl, HBr or HNO 3 ) [38][39][40] where at least four water molecules seemed to be required to stabilize the ionic pair formed. We find here a similar effect, albeit with a smaller hydration number, for HCl.…”
Section: Proton Transfermentioning
confidence: 99%
“…One inquiry that persistently threads its way through this subject is: what is the minimum quantity of water molecules, (H 2 O) n , required to dissociate the acid [18]? According to calculations, the acidically dissociated structure is supported starting from n=4; most of the theoretical approaches agree that at this size the dissociated form represents the global minimum on the potential energy surface [18][19][20][21][22][23][24]. Experimentally, for neutral clusters the question has been probed by laser spectroscopy (see, e.g., [25][26][27][28]) but finding a conclusive spectroscopic signature of the onset of dissociation in a nanocluster is not straightforward.…”
Section: Introductionmentioning
confidence: 99%